2009
DOI: 10.1182/blood-2008-06-162610
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of the β1-tubulin gene associated with congenital macrothrombocytopenia affecting microtubule assembly

Abstract: Congenital macrothrombocytopenia is a genetically heterogeneous group of rare disorders. We identified the first TUBB1 mutation, R318W, in a patient with congenital macrothrombocytopenia. The patient was heterozygous for Q43P, but this single-nucleotide polymorphism (SNP) did not relate to macrothrombocytopenia. Although no abnormal platelet ␤1-tubulin localization/marginal band organization was observed, the level of ␤1-tubulin was decreased by approximately 50% compared with healthy controls. Large and irreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
141
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(157 citation statements)
references
References 19 publications
10
141
6
Order By: Relevance
“…However, some protein functions currently remain unknown (SLFN14 and GNE). [4][5][6][7][8][9] . Although our knowledge of the causes of IT continues to grow, presently a genetic diagnosis is only reported in approximately 50% of individuals.…”
Section: Whole Exome Sequencing Identifies Genetic Variants In Inherimentioning
confidence: 99%
“…However, some protein functions currently remain unknown (SLFN14 and GNE). [4][5][6][7][8][9] . Although our knowledge of the causes of IT continues to grow, presently a genetic diagnosis is only reported in approximately 50% of individuals.…”
Section: Whole Exome Sequencing Identifies Genetic Variants In Inherimentioning
confidence: 99%
“…The principle of benzimidazole resistance is closely associated with point mutations in the β-tubulin genes that change the structure of the fungicide-binding point (Gafur et al 1998;Albertini et al 1999;Peres et al 2004;Chung et al 2006;Davidson et al 2006;Ziogas et al 2009). T274I, R282Q, and Q292E mutations significantly weakened the interactions and binding of the drugs taxol and epothilone (Natarajan and Senapati 2012), while Q43P and R318W mutations had a significant impact on platelet physiology in immune thrombocytopenia (Freson et al 2005;Kunishima et al 2009;NavarroNunez et al 2011). The genetics of carbendazim resistance in Aspergillus nidulans (van Tuyl 1977), Ustilago maydis (Ziogas and Girgis 1993) and other fungal species revealed that in most cases it was based on a single gene.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the key role of microtubules in PPF, mutation of a component of the microtubule system was identified in only one family with IT [3]. The p.R318W change in b1-tubulin was predicted to affect microtubule assembly by disrupting interaction between a-and b-tubulin to form heterodimers.…”
Section: Defective Ppf From Mature Mksmentioning
confidence: 99%
“…2). BM examination is not required for diagnosis of these forms: however, in the few analyzed cases, it demonstrated normal or increased number of mature Mks with normal morphology [3,44,45].…”
Section: Defective Ppf From Mature Mksmentioning
confidence: 99%
See 1 more Smart Citation